Effects of Cr6+ stress on chromium chemical speciation distribution and bacterial community structure in the Coix lacryma-jobi L. constructed wetlands. Issue 1 (31st December 2022) - Fang, Zirui; Wang, Qianyun; Zhang, Cunqi; Li, Suli; Li, Shuai; Wang, Xueli; Cheng, Xiran; He, Zhenli; Li, Zhigang
ABSTRACT: In this study, micro Coix lacryma-jobi L. vertical flow constructed wetlands with 0, 10 and 30 mg/L Cr 6+ (in the form of K2 Cr7 O2 ) in the water sources were constructed to study the purification efficiency of chromium-contaminated wastewater, bacterial community diversity, chromium chemical speciation distribution and other indicators. The results showed that the constructed wetlands had high purification efficiency for chromium-contaminated wastewater. The removal rate of Cr 6+ reached 99.61% and 95.45% in 10 and 30 mg/L Cr 6+ treatment. The bacterial diversity index was unaffected by Cr 6+ treatment; however, the bacterial richness index declined dramatically as Cr 6+ treatment concentration increased. The bacterial community structure was influenced by the substrates pH, moisture content, organic matter and total chromium content. The abundance of Burkholderiaceae (uncultured) and Saccharimonadales (uncultured) were positively correlated with non-residual chromium content. The results contributed to understand the effect of chromium on bacterial community structure by considering the chromium chemical speciation.